DIGITAL TRANSFORMATION AND INNOVATION IN ISLAMIC EDUCATION: ADDRESSING THE CHALLENGES OF THE CYBER-PEDAGOGY ERA - Rofiatul Hosna; R. Suyato Kusumaryono; Titin Nurhidayati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Digital transformation in Islamic education is no longer merely an option, but a necessity to maintain relevance in the era of cyber-pedagogy. This study aims to analyze the integration of digital technology in learning at Islamic educational institutions and its impact on curriculum innovation and teaching methods. Using a literature review method, data was collected from various reputable scientific literature indexed on the SINTA and Scopus platforms. The results indicate that digital transformation in Islamic educational institutions manifests through the implementation of cloud-based learning management systems (LMS), the use of interactive artificial intelligence (AI) media, and the digitization of Islamic educational materials. These innovations have successfully improved administrative efficiency, expanded access to learning resources, and increased student engagement. However, the main obstacles faced include digital infrastructure gaps between regions, limited technological competencies among teachers, and challenges in maintaining the authenticity of the internalization of moral values in a virtual setting. This study concludes that the success of digital-based Islamic educational innovation requires synergy between infrastructure readiness, the enhancement of educators’ cyber-pedagogy competencies, and a curriculum adaptation that strikes a balance between science and technology (iptek) and religious values (imtaq).